2002
DOI: 10.1159/000064117
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial Relationship of γ-Aminobutyric Acid (GABA) Neurons and Gonadotropin-Releasing Hormone (GnRH) Neurons in Larval and Adult Sea Lamprey, <i>Petromyzon marinus</i>

Abstract: In this study we examined the spatial relationship of GABA-containing and GnRH-containing neurons by immunocytochemistry and in situ hybridization in larval and adult brains of sea lamprey, Petromyzon marinus. In immunocytochemical studies, GABA-containing neurons were detected early in lamprey development, by day 20 post-fertilization. At this time point, one population of GABA-containing neurons was visualized in the hypothalamus and preoptic area, and another population was located in the olfactory bulb of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
21
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 57 publications
11
21
0
Order By: Relevance
“…The α-decarboxylation of L-glutamic acid is a primary step in GABA synthesis and this reaction is catalysed by GAD (Reed et al 2002). The present findings suggest that an appropriate amount of MSG can stimulate GABA production.…”
Section: Identification Of Significant Variables By Plackett-burman Dsupporting
confidence: 53%
“…The α-decarboxylation of L-glutamic acid is a primary step in GABA synthesis and this reaction is catalysed by GAD (Reed et al 2002). The present findings suggest that an appropriate amount of MSG can stimulate GABA production.…”
Section: Identification Of Significant Variables By Plackett-burman Dsupporting
confidence: 53%
“…It is not clear whether GnRH I produced by the hypothalamus or by other tissues binds to and signals through these receptors throughout the body. At least for the brain, GnRHR I signaling is likely mediated through GnRH I produced by GnRH I neurons that extend throughout different regions of the brain (Tobet et al 1996, Quanbeck et al 1997, Kim et al 1999, Reed et al 2002. The short serum half-life of GnRH I (approximately 2-3 min; Redding et al 1973, Fauconnier et al 1978 would support autocrine release of GnRH I within the brain, although it has been shown in rats that GnRH I can cross the blood brain barrier (BBB) (Dvorska et al 1992).…”
Section: Functional Consequences Of Gnrh I Induction Of Lh Expressionmentioning
confidence: 99%
“…Few studies have examined the role of GABA on GnRH in fish and to date, only one previous study has examined the possibility of GABA-GnRH interactions in the hypothalamus of the sea lamprey. Previous immunocytochemical studies by Reed et al [2002] demonstrated the close spatial relationship between GABA-containing neurons and GnRH-containing neurons in the hypothalamus of the larval sea lamprey, hypothesizing that GABA is directly involved in controlling GnRH release. Using in situ hybridization, Reed et al also showed the expression of the GABA-synthesizing enzyme glutamic acid decarboxylase (GAD) in close proximity to cells expressing GnRH-I in the hypothalamus of larval sea lamprey, although no comparisons between the expression of GAD and GnRH were made in the juvenile and adult sea lamprey.…”
Section: Introductionmentioning
confidence: 97%
“…Numerous immunocytochemistry (ICC) studies [Crim et al, 1979a, b;Nozaki and Kobayashi, 1979;Nozaki et al, 1984Nozaki et al, , 2000King et al, 1988;Wright et al, 1994;Tobet et al, 1995Tobet et al, , 1996Reed et al, 2002] have investigated the distribution of lamprey GnRH in the brain of several lamprey species. These studies have consistently demonstrated the localization of lamprey GnRH-I and -III in the preoptic area and hypothalamus extending to the neurohypophysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation